Construction of an integrative regulatory element and variation map of the murine Tst locus. Issue 1 (December 2016) - Beltram, Jasmina; Morton, Nicholas; Kunej, Tanja; Horvat, Simon
Abstract Background Given the abundance of new genomic projects and gene annotations, researchers trying to pinpoint causal genetic variants are faced with a challenging task of how to efficiently integrate all current genomic information. The objective of the study was to develop an approach to integrate various genomic annotations for a recently positionally-clonedTst gene (Thiosulfate Sulfur Transferase, synonym Rhodanese) responsible for theFob3b2 QTL effect on leanness and improved metabolic parameters. The second aim was to identify and prioritizeTst genetic variants that may be causal for the phenotypic effects. Results A bioinformatics approach was developed to integrate existing knowledge of regulatory elements of theTst gene. The entireTst locus along with flanking segments was sequenced between our unique polygenic mouse Fat and Lean strains that were generated by divergent selection on adiposity for over 60 generations. The bioinformatics-generated regulatory element map of theTst locus was then combined with genetic variants between the Fat and Lean mice and with comparative analyses of polymorphisms across 17 mouse strains in order to prioritise likely causal polymorphisms. Two candidate regulatory variants were identified, one overlapping an evolutionary constrainedTst intronic element and the other residing in the seed region of a predicted 3′UTR miRNA binding site. Conclusions This study developed a map of regulatory elements for theTst locus in mice and identified candidate genetic variants with increased causal likelihood. This map provides a basis for experimental validation and functional analyses of this novel candidate leanness and antidiabetic gene. Our methodological approach is of general utility for analyzing regulation of loci that have limited annotations and experimental evidence and for identifying candidate causal regulatory genetic variants in post-GWAS or post-QTL- cloning studies.